Implementation of negative pressure for acute pediatric burns (INPREP): A stepped-wedge cluster randomized controlled trial protocol. - Maleea D Holbert; Fiona Wood; Andrew J A Holland; Warwick Teague; Roy M Kimble; Dianne Crellin; Cody C Frear; Kristen Storey; Natalie Phillips; Yvonne Singer; Tanesha A Dimanopoulos; Lisa Martin; et al. (PLoS ONE)
Background Acute application of adjunctive negative pressure wound therapy (NPWT) significantly improves time to re-epithelialization in pediatric burn patients. This adjunctive treatment has not yet been broadly or routinely adopted as a standard primary burns dressing strategy. The Implementation of Negative PRessurE for acute Pediatric burns (INPREP) trial will implement and evaluate the impact of adjunctive NPWT in parallel with co-designed implementation strategies and resources across four major pediatric hospitals. Methods We will conduct a multi-center, prospective, stepped-wedge cluster randomized controlled trial to implement adjunctive NPWT for acute pediatric burns. Participants will include pediatric burn patients presenting to one of four Australian tertiary pediatric hospitals for burn treatment. The intervention is adjunctive NPWT in parallel with co-designed and tailored implementation strategies and a suite of NPWT implementation resources, which form the INPREP toolkit. Using a hybrid type III design, this trial aims to evaluate the effectiveness of NPWT implementation in parallel with the INPREP toolkit using (i) implementation outcomes (e.g., adoption, appropriateness, acceptability, feasibility, and sustainability) and (ii) clinical outcomes (e.g., days to re-epithelialization, scar management requirements, skin grafting requirements). The primary outcome of this trial is treatment adoption-the proportion of eligible patients who receive NPWT. Discussion This manuscript outlines a protocol for a hybrid type III stepped-wedge cluster randomized controlled trial of adjunctive NPWT implementation in acute pediatric burn care. We anticipate that NPWT implementation in parallel with the INPREP toolkit will be generalizable to emergency departments and burn services across Australia, and evidence generated will inform pediatric burn care internationally. Trial registration Australian and New Zealand Clinical Trials Registry: ACTRN12622000166774. Registered 1 February 2022.